Can Weightbearing Computed Tomography Scans Be Used to Diagnose Subtalar Joint Instability? A Cadaver Study. Issue 11 (6th August 2019) - Krähenbühl, Nicola; Burssens, Arne; Davidson, Nathan P.; Allen, Chelsea McCarty; Henninger, Heath B.; Saltzman, Charles L.; Barg, Alexej
ABSTRACT: Chronic hindfoot instability is a frequent problem that includes the ankle and/or the subtalar joint. While ankle joint instability can be diagnosed clinically, accurate assessment of the subtalar joint remains elusive. This study's purpose was to assess the ability of weightbearing computed tomography (CT) scans to detect subtalar joint instability. Seven pairs of fresh frozen male cadavers (tibial plateau to toe‐tip) were tested. A radiolucent frame held specimens in a plantigrade position while non‐weightbearing and weightbearing CT scans (with and without torque application) were taken. First, intact ankles (Native) were scanned. Second, one specimen from each pair underwent interosseous talo‐calcaneal ligament (ITCL) transection, while the contralateral underwent calcaneo‐fibular ligament (CFL) transection. Third, the remaining intact ITCL or CFL was transected. Finally, the deltoid ligament was transected in all ankles. Eight radiographic measurements were performed to assess the congruency of the subtalar joint on digitally reconstructed radiographs and single CT images. Axial loading did not impact most measurements, whereas torque did impact most measurements. Radiographic measurements performed at the subtalar joint level were more reliable and better predictors for subtalar joint instability compared with measurements performed at the ankle joint level. While torque application is crucial to identify subtalar joint instability, axial load application should be avoided. Measurements to assess the subtalar joint stability should primarily be performed at the subtalar joint level rather than at the ankle joint level when using weightbearing CT scans. © 2019 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 37:2457–2465, 2019